2018
DOI: 10.1093/neuros/nyx636
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Nerve Compression Without Trigeminal Neuralgia: Intraoperative vs Imaging Evidence

Abstract: There was moderate agreement between imaging and operative findings with respect to both the presence and severity of NVC/C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…In our study, we found similar results that the atypical TN patients achieved a lower rate of excellent pain relief. Previous studies showed that vascular contact with the trigeminal nerve is universal (occurring in 82 to 92%) [15]. Nevertheless, several papers showed that neurovascular compression on MRI remains important for predicting postoperative outcome following MVD [22,29].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found similar results that the atypical TN patients achieved a lower rate of excellent pain relief. Previous studies showed that vascular contact with the trigeminal nerve is universal (occurring in 82 to 92%) [15]. Nevertheless, several papers showed that neurovascular compression on MRI remains important for predicting postoperative outcome following MVD [22,29].…”
Section: Discussionmentioning
confidence: 99%
“…Literature reveals considerable interest in characterization of CNs in assessment of various skull base pathologies, including pituitary adenomas, 7,14 trigeminal neuralgia, [17][18][19] vestibular schwannomas, 20,21 and among others. 22 Those studies have examined conventional imaging 7,17,18 and advanced sequences, such as diffusion tensor imaging (DTI) [19][20][21][22] in CN assessment. This study indicates that several CNs are better imaged at 7 T MRI compared with conventional MRI, suggesting that this technology could aid in localization and protection of nerves intraoperatively.…”
Section: Imaging the Cranial Nervesmentioning
confidence: 99%
“…The pathogenesis of “classical TN (cTN)” is frequently attributed to hyperexcitability of trigeminal ganglion neurons ( Burchiel, 1980a , 1980b ; Burchiel and Baumann, 2004 ; Devor et al., 2002 ) secondary to morphological compression of the trigeminal nerve root entry root by the cerebral vasculature (i.e., neurovascular compression [NVC]) ( Headache Classification Committee of the International Headache Society (IHS), 2013 ; Cruccu et al., 2016 ; Gardner and Miklos, 1959 ; Hilton et al., 1994 ; Rappaport et al., 1997 ). However, asymptomatic NVC has been noted in ∼13%–85% of asymptomatic subjects ( Haines et al., 1980 ; Hamlyn, 1997a , 1997b ; Jani et al., 2019 ). Other cases of TN are related to trigeminal nerve infection (e.g., herpes zoster), trauma, demyelination (as in multiple sclerosis), or compression from a space-occupying lesion in the cerebello-pontine angle and are termed “secondary TN.” However, a significant number of TN cases lack a demonstrable cause (“idiopathic TN [iTN]”) ( Hughes et al, 2019 ; Maarbjerg et al., 2017 ), including some cases with bilateral symptoms ( Brisman, 1987 ; Pollack et al., 1988 ).…”
Section: Introductionmentioning
confidence: 99%